Identification of a New Theca/Interstitial Cell-Specific Gene and Its Biological Role in Growth of Mouse Ovarian Follicles at the Gonadotropin-Independent Stage - Aoyama, Masato; Shiraishi, Akira; Matsubara, Shin; Horie, Kaoru; Osugi, Tomohiro; Kawada, Tsuyoshi; Yasuda, Keiko; Satake, Honoo (Frontiers in Endocrinology, 2019)
Theca/interstitial cells are responsible for the growth and maturation of ovarian follicles. However, little is known about the theca/interstitial cell-specific genes and their functions. In this study, we explored transcriptomes of theca/interstitial cells by RNA-seq, and the novel biological roles of a theca cell marker, asporin (Aspn)/periodontal ligament-associated protein 1 (PLAP-1). RNA-seq detected 432 and 62 genes expressed specifically in theca/interstitial cells and granulosa cells isolated from 3-week old mouse ovaries. Gene ontology analysis demonstrated that these genes were largely categorized into four major groups: extracellular matrix organization-related terms, chemotaxis-related terms, the angiogenesis-related terms and morphogenesis-related terms. In situ hybridization demonstrated that the newly detected representative gene, Aspn/PLAP-1, was detected specifically in the outer layer of theca cells in contrast with the expression of the basal lamina-specific gene, Nidgen-1. Intriguingly, an Aspn/PLAP-1 antibody completely arrested the growth of secondary follicles that is the gonadotropin-independent follicle developmental stage. Furthermore, transforming growth factor-β (TGF-β)-triggered signaling was induced by the Aspn/PLAP-1 antibody treatment, which is consistent with the inhibitory effect of Aspn/PLAP-1 on TGF-β. Altogether, these results suggest that theca cells are classified into subpopulations on the basis of new marker genes and their biological functions, and provide evidence that Aspn/PLAP-1 is expressed exclusively in the outer layer of theca cells and plays a pivotal role in the growth of secondary follicles via downregulation of the canonical TGF-β signaling cascade.